2012
DOI: 10.3897/compcytogen.v6i3.3019
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the chromosome G-banding pattern in two Sorex species, S. satunini and S. araneus (Mammalia, Insectivora)

Abstract: The G-banded karyotype of Sorex satunini was compared with the karyotype of Sorex araneus. Extensive homology was revealed. The major chromosomal rearrangements involved in the evolutionary divergence of these species have been identified as centric fusions and centromeric shifts. From the known palaeontological age of Sorex satunini it is obvious that the vast chromosomal polymorphism of the Sorex araneus group originated during the middle Pleistocene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…araneus because it shows the most primitive karyotype, which is characterized by polymorphic metacentric fusion j:l and more acrocentric chromosomes than other races [ 30 , 35 ]. The data concerning the rearrangements and chromosomal characters was taken from appropriate references [ 9 , 16 , 77 79 ], including the newest one based on Zoo-FISH hybridization [ 19 ]. We analysed 29 available chromosomal rearrangement characters by maximum parsimony approach in PAUP and Bayesian in MrBayes.…”
Section: Methodsmentioning
confidence: 99%
“…araneus because it shows the most primitive karyotype, which is characterized by polymorphic metacentric fusion j:l and more acrocentric chromosomes than other races [ 30 , 35 ]. The data concerning the rearrangements and chromosomal characters was taken from appropriate references [ 9 , 16 , 77 79 ], including the newest one based on Zoo-FISH hybridization [ 19 ]. We analysed 29 available chromosomal rearrangement characters by maximum parsimony approach in PAUP and Bayesian in MrBayes.…”
Section: Methodsmentioning
confidence: 99%
“…However, a recent study by Borisov and Orlov (2012) comparing the G-banded karyotypes of Sorex satunini and S. araneus revealed major chromosomal rearrangements (S. satunini has a more rearranged karyotype than the species of the S. araneus group in Western Europe) what implied their evolutionary divergence. According to these authors, the number of chromosome rearrangements shared by the species of the Sorex "araneus" group suggests an Early Pleistocene common ancestor.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that some fusions, for instance gh and hm absent in the h (as well as g and m ) series, were found outside the current list of chromosomal races. These are hm , present in an F1 interracial hybrid karyotype due to proposed whole arm reciprocal translocation ( WART ) ( Pavlova et al 2008 ), and gh , identified in the karyotype of a sibling species, S. satunini Ognev, 1922 ( Borisov and Orlov 2012 ). Besides, it seems remarkable that the chromosomes o and q , most “active” in fusions, are carriers of nucleolus organizing region ( NOR ), located distally at an acrocentric end ( Searle et al 1991 ).…”
mentioning
confidence: 99%